PENGARUH PERSEPSI MASYARAKAT PADA CALEG TERHADAP PERILAKU MEMILIH DALAM PEMILIHAN LEGISLATIF 2014 DI SIDOARJO - Yusuf, Ahmad (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article scrutinizes the effect of public’s perception towards legislative candidates in the 2014 local legislative elections in Sidoarjo. Thereis an assumption which perceives that people have their own awareness to choose candidates directly without being influenced by the political parties. This means that legislative candidates posses the same rights in terms of their electability. Using quantitative approach, the results of the research show that the effect between people’s perception towards the candidates along with the voting behavior in the 2014 legislative elections has been “strong enough”on the voting behavior in the 2014 legislative elections in Sidoarjo by 0.454. In other words, 45% of voting behavior has been influenced by public’s perception towards the candidates and 55% of voting behavior was influenced by other factors.